Evaluation of age group and sex differences in the measurement of patellar height of pediatric knee in a Korean population - Kwak, Yoon Hae; Park, Soo-Sung; Huser, Aaron J.; Lim, Hyo Won; Baki, Sharkawy wagih Abdel; Koh, Yong-Gon; Nam, Ji-Hoon; Kang, Kyoung-Tak (Frontiers in Pediatrics, 2023)
Introduction Various methods based on bony landmarks are used to determine patellar height. This study analyzed five methods for patellar height measurement on lateral knee radiographs, namely, the Insall–Salvati, Koshino–Sugimoto, Blackburne–Peel, modified Insall–Salvati, and Caton–Deschamps methods. Methods Overall, 425 pediatric participants (221 males, 204 females; age range 5–18 years) were included and were divided equally into three age groups (A, 5–10 years; B, 11–13 years; and C, 13–18 years). For the comparison of the applicability of each method, the applicable probabilities for each age group and sex-based differences were analyzed using logistic regression techniques. Intra-rater reliability and inter-rater variability were analyzed by two trained raters. Results The Koshino–Sugimoto method was applicable to all patients. The 80% applicable age of female patients was lower than that of male patients for the Blackburne–Peel (male=11.9, female=11) and Caton–Deschamps (male=11.9, female=11.1) methods. However, in the Insall–Salvati (male=12, female=12.1) and modified Insall–Salvati (male=12.6, female=13.1) methods, the 80% applicable age in male patients was lower than that in female patients. The Koshino–Sugimoto method showed the highest variability in group B, while the Insall–Salvati showed the highest variability in group C. In terms of intra-observer reliability, the Caton–Deschamps method showed the same reliability as the Insall–Salvati method, in group C. Conclusions Our results demonstrated differences in the reliability, variability, and applicability of patellar height measurement methods according to age group. The applicability of patellar height measurement methods also differed according to sex. Therefore, based on age group and sex, different methods should be used for patellar height measurement in pediatric patients.